Theoretical study on the electronic structure nature of single and double walled carbon nanotubes and its role on the electron transport. Issue 17 (27th May 2019) - Espinosa‐Torres, Néstor David; Guillén‐López, Alfredo; Martínez‐Juárez, Javier; Hernández de la Luz, José Álvaro David; Rodríguez‐Victoria, Ángel Pedro; Muñiz, Jesús
Abstract: Density functional theory and molecular dynamics (MD) calculations were used to evaluate electronic structure properties in a series of nanotubes with smallest possible diameters (both types: armchair and zigzag), and the corresponding chiral nanotubes (8, m) for 0 ≤ m ≤ 8. The calculations were performed considering a length of 16.5 Å. We evaluated a set of 26 combinations of dual nanotubes (armchair/armchair, zigzag/zigzag, armchair/zigzag, and zigzag/armchair), where the first label corresponds to the outer tube. We extended our study with nine additional systems of double‐walled carbon nanotubes (DWCNT) with semiconductor nature. In this regard, we gave insight into the semiconductive or metallic nature inherited to the dual tubes. DWCNT systems were possible to construct by maintaining a radial distance of 3.392 Å for the armchair/armchair arrangement and 3.526 Å for the zigzag/zigzag type. It was considered as a reference, the interplanar distance of graphite (3.350 Å). Electronic transport calculations were also performed on selected DWCNT systems in order to understand the role played by the different symmetries under study. It was evidenced that the electronic structure nature of the systems rules the ability to transport electrons through the DWCNT interface. Abstract : A combined ab initio and molecular dynamics methodology was proposed to predict the electronic structure nature in an ensemble formed by two carbon nanotubes. Electronic transport assessment through the interface reveals the presence of trap states that may inhibit the electron transfer. The metallic or semiconducting nature of the carbon components in the ensemble rules such behavior. This theoretical scheme may aid to tailor carbon‐based materials to be applied in several solid‐state devices.